National Libyan records on blood cellular elements of the Long-eared hedgehog (Hemiechinus auritus) - Ibrahim , Laila A.; Ilfergane, Abdulkarem A.; Tawfeeq , Nadhima A.J. (Scientific Journal of University of Benghazi, 2023)
This study is an attempt to describe some aspects relating to the blood cells of one of Libya's wildlife animals, the long-eared hedgehog (Hemiechinus auritus). The investigation focused on the morphology of the blood cells in newborn and adult animals that were obtained from the city of Benghazi. Four one-day-old hedgehoglets and 20 adult hedgehogs were utilised to prepare stained blood smears. Structural features of blood cells of both young and adult animals did not show prominent variations from each other. Neutrophils nuclei had a band and multilobulated appearance. The maximal number of nuclear lobes reached seven in the newborn hedgehogs and eight in the adult and the joining threads between the lobes were mostly very obvious. The Barr body could not be observed in neutrophils of the female animals. Non-lobulated nuclei were encountered in the eosinophils of the adult animals, whereas the nuclear trilobulation could be noticed in the eosinophils of both groups of hedgehogs. Basophils of the newborn hedgehogs showed large irregular nuclei, whereas those of the adults had partially divided indented nuclei. Small, medium and large lymphocytes could be observed in blood films of the newborn and adult animals. However, the majority of the lymphocytes were small in size. Eccentrically located nuclei with kidney-shaped, horseshoe, oval and round appearances were recorded in monocytes of both groups of animals. Platelets of the newborn and adult hedgehogs were non-nucleated and had round to oval shapes. A centrally located dark area surrounded by a less dense area was obvious. The discoid non-nucleated erythrocytes had a biconcave appearance in both groups of hedgehogs.